Spatial restructuring through poverty alleviation resettlement in rural China. (October 2016) - Lo, Kevin; Xue, Longyi; Wang, Mark
Abstract: Poverty alleviation resettlement (PAR) is one of China's key poverty reduction initiatives. Through this state-led resettlement programme, the government aims to improve the living standards and access to infrastructure and services of the rural poor. This paper examines PAR from the perspective of spatial restructuring through a household survey conducted in Shanxi and Shaanxi provinces. A total of 30 resettlement sites were examined. The results show that PAR has two spatial forms: long-distance resettlement, which resettles people to cities or towns, and short-distance resettlement, which resettles people within the administrative boundaries of their village or to a nearby village. Furthermore, the type of spatial restructuring is an important factor shaping the outcome of resettlement. While long-distance resettlement outperforms short-distance resettlement in terms of gains in income, the advantage is offset by higher post-resettlement expenses. Furthermore, long-distance resettlers face a greater challenge in securing non-agricultural employment. Consequently, the level of satisfaction is lower among long-distance resettlers. Significant challenges remain to be addressed for both types of resettlement, including establishing two-way communication between villagers and the government about resettlement plans and providing better financial support for the resettlers, safeguards for the livelihoods of non-movers, and post-resettlement support programmes to help resettlers adjust to their new environments. Highlights: Poverty alleviation resettlement (PAR) is a key type of spatial restructuring in rural China. PAR has two spatial forms: long-distance resettlement and short-distance resettlement. The type of spatial forms is an important factor shaping the outcome of resettlement.